Biomechanical Analysis of Restored Teeth with Cast Intra-Radicular Retainer with and Without Ferrule - Poiate, Isis Andréa Venturini Pola; Junior, Edgard Poiate; Ballester, Rafael Yagϋe (IntechOpen, 2012)
None